Bt cotton - a safe and profitable option? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Dr Ousmane Coulibaly of the International Institute for Tropical Agriculture on the risks and potential of genetically modified (Bt) cotton.